O Traço Divino - a geometria como instrumento de sacralização do espaço na igreja de Santa Maria Maior - Miguel Valido Chaves Pereira (2015)
The aim of this work is to clarify the metaphysical implications of the use of geometryin sacred architecture, both in general and in the particular case of the church of Santa MariaMaior, Lisbon Cathedral.It begins with a research on the connections between geometry, architecture and thesacred, in order to show in what ways sacred architecture and sacred geometry cometogether in a scheme which regulates the physical, architectural form according tometaphysical principles.It is followed by a brief account of the cathedral's history that will inform itsgeometrical analysis. Knowing its physical evolution and the historical context of the mainconstruction phases will help evaluating the validity of the analysis' results.The geometrical analysis shows two very convincing geometric schemes: one for theRomanesque church and another for the gothic ambulatory. The Romanesque scheme isbased on the ad quadratum development of a square with a side of 7,7m centred on thecrossing. The gothic work is defined by a scheme of inscribed heptagrams traced around themain chapel's 7-sided apse. The metaphysical value of the first scheme is the underlyingreflection on the foundation of the World, which is symbolically repeated in the foundationof the church. The value of the second scheme is not so clear to read, but it may be related tothe incredible symbolic power of the number Seven.